Genetic Control of Susceptibility to Cryptococcus neoformans in Mice - Rhodes, Judith C. (1980)
Inbred mice injected intravenously with 5 × 10(6) cells of Cryptococcus neoformans showed two patterns of survival: sensitive (A/WySn, A.BY, A/J, DBA/2J, NZB/B1NJ, and SWR/J) and resistant [C57BL/10Sn, B10.A, B10.A (2R), B10.S (7R),C57BR/cdJ, C58/J, C3H/HeJ, BALB/c, DBA/1J, and SJL/J]. Relative susceptibility based on survival time was shown to correspond to differences obtained for 50% lethal dose values. Either decreasing the dose of organisms or changing to the intraperitoneal route of inoculation resulted in prolonged survival times, but neither change affected the observed patterns of survival. F1 hybrids between different sensitive strains were also sensitive, whereas F1 hybrids between sensitive and resistant strains were resistant, indicating a dominant mode of inheritance. Sensitivity and resistance were shown to be under single gene control by segregation analysis in F2 progeny produced by inbreeding (B10.A × A/WySn)F1 hybrids and in (F1 × A/WySn) backcross progeny. Blood obtained from parental strains, F1, F2, and backcross hybrids was tested for the presence or absence of hemolytic complement. Mice lacking hemolytic complement activity in their sera are homozygous for the Hc(0) allele at the Hc locus on chromosome 2 and are deficient in the complement component C5. A 1:1 correspondence was found between C5 deficiency and sensitivity to C. neoformans. Resistance was shown to cosegregate with the presence of hemolytic complement in the F2 and the backcross progenies.